Analisis Peran dan Tantangan Sukuk Hijau Bagi Ketahanan Perubahan Iklim Pada Wilayah Rentan Selama Pandemi Covid-19 - Ahmad Fawaiq Suwanan; Syahrul Munir; Santi Merlinda (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Sovereign Sukuk has become a promising instrument for a country to overcome difficulties in financing government projects. Sukuk is a financial instrument for the Islamic capital market with a low level of risk. Green sukuk becomes popular since most of the conventional investment activities ignore the environment aspect. Starting in 2018, Indonesian government has developed a green sukuk scheme as a financing instrument for environmentally friendly projects to reduce the impact of global climate change. This study aims to analyze the role and challenges of green sukuk for climate change resilience in highly vulnerable areas during the Covid-19 crisis. This study is conducted through a qualitative method with a phenomenological approach. Data collections are carried out through literature studies and case studies on some climate projects in highly vulnerable areas in Indonesia. The results show that during the Covid-19 pandemic, green sukuk has contributed an important impact for climate change resilience in highly vulnerable areas. There are some challenges in the development of green sukuk. The lack of awareness of social risks as well as environmental risks have become main challenges. In the future, the decision policy makers should provide greater incentives and a more inclusive legal umbrella for green financing schemes.